Pengaruh Persepsi Gaya Kepemimpinan dan Sifat Kepribadian pada Persepsi Intensitas Konflik di GKJW Jemaat Madiun. - , Natael Hermawan Prianto, Prof. Dr. Djamaluddin Ancok, MA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Organizational conflict can be triggered by the different perceptions and opinions of the individual, leadership styles, personality characteristics that cause individuals are unique (idiosyncrasies) and different from other individuals, job dependency, vagueness of the task, and communication. This study aims to examine whether there is influence perceptions of leadership styles (transactional and transformational leadership style) and Big Five Personality traits on the perception of the intensity of the conflict in GKJW Madiun. The subject of this research is a member of GKJW Madiun, where the sample is done by using nonprobabilitas with convenience sampling technique for 300 respondents. Collecting data in this study conducted by distributing a questionnaire (a list of statements) on the perception of the intensity of conflict, perceptions of leadership style, and personality traits. Data obtained in this study were measured by using a Likert Scale. The analysis technique used in this research is analysis descriptive statistics and inferential statistical analysis (multiple linear regression and t test). The results showed that the perception of transformational leadership style has a significant negative influence on the perception of the intensity of conflict in the GKJW Madiun (significance value of 0.000). Another result is that the variable Conscientiousness had a significant positive effect on perceptions of conflict intensity (value of significance 0.042).